Correlation of leukocyte count with length of hospitalization in bronchopneumonia patients - Arumsari, Rizqi Amalia; Bungin, Cristian; Haikal, Sayyid Muhammad Sahil; Satriadi, Joda Isham; Ramadhanurrosita, Nia; Munif, Achmad; Mildawati, Mildawati; Amran, Andhika; Hamidah, Izdihar Nafi’u; Siahaan, Ina Uli Tondi Tarigas; Priska, Novia; Simatupang, Nurfatimah Aprillianda; Arista, Tiara; Zahra, Hanna; Tagamawan, Astra Yudha (Pediatric Sciences Journal, 2024)
Introduction: Pneumonia is a disease characterized by inflammation or infection of the lung parenchyma. In the process of inflammation or infection, there are agents involved that serve as the body’s defense against infection, such as leukocytes. Leukocytes can be used as a parameter to assess the severity of the disease, which is one of the factors affecting the length of hospital stay for pneumonia patients, particularly in young children. This study aims to determine the correlation between the leukocyte count and the length of hospital stay in patients with bronchopneumonia at RSUD dr. Abdul Rivai Berau. Methods: This research was an analytical observational study with a retrospective cohort approach and used consecutive sampling for data collection. Result: The results indicate that 935 subjects meet the inclusion and exclusion criteria. Data analysis using the Pearson correlation test yielded a p-value of 0.029 and an R-value of 0.072. Conclusion: There is a correlation between leukocyte count and the length of hospital stay in bronchopneumonia patients.